Attentional bias towards social interactions during viewing of naturalistic scenes - Skripkauskaite, S; Mihai, I; Koldewyn, K (SAGE Publications, 2022)
Human visual attention is readily captured by the social information in scenes. Multiple studies have shown that social areas of interest (AOIs) such as faces and bodies attract more attention than non-social AOIs (e.g., objects or background). However, whether this attentional bias is moderated by the presence (or absence) of a social interaction remains unclear. Here, the gaze of 70 young adults was tracked during the free viewing of 60 naturalistic scenes. All photographs depicted two people, who were either interacting or not. Analyses of dwell time revealed that more attention was spent on human than background AOIs in the interactive pictures. In non-interactive pictures, however, dwell time did not differ between AOI type. In the time-to-first-fixation analysis, humans always captured attention before other elements of the scene, although this difference was slightly larger in interactive than non-interactive scenes. These findings confirm the existence of a bias towards social information in attentional capture and suggest our attention values social interactions beyond the presence of two people.